Coping behavior of junior physicians in managing conflict between work and family roles - Ahmad, Aminah (Marsland Press, 2011)
This study examined the extent of work-family conflict experienced by married female junior physicians and the coping behavior of the physicians in managing the conflict. The sample of this study consisted of married female physicians (with at least one child) aged 40 and below working in fourteen public hospitals in Malaysia. Data were gathered from a sample of 231 female junior physicians using self-administered questionnaires through the drop and collect method. The two major strategies used by the physicians were personal role redefinition which involved changing their own attitudes and perceptions of role expectations, and reactive role behavior which involved careful planning, scheduling and organizing their role activities, and working harder to meet all their role demands. The least frequently used strategy was structural role redefinition which entails an active attempt to deal directly with role senders and lessen the conflict by mutual agreement on a new set of expectations. Implications of the findings and suggestions for future research were discussed.